Direct reticular projections of trigeminal sensory fibers immunoreactive to CGRP: potential monosynaptic somatoautonomic projections - Panneton, W. Michael; Gan, Qi (Frontiers in Neuroscience, 2014)
Few trigeminal sensory fibers project centrally beyond the trigeminal sensory complex, with only projections of fibers carried in its sensory anterior ethmoidal (AEN) and intraoral nerves described. Fibers of the AEN project into the brainstem reticular formation where immunoreactivity against substance P and CGRP are found. We investigated whether the source of these peptides could be from trigeminal ganglion neurons by performing unilateral rhizotomies of the trigeminal root and looking for absence of label. After an 8-14d survival, substance P immunoreactivity in the trigeminal sensory complex was diminished, but we could not conclude that the sole source of this peptide in the lateral parabrachial area and lateral reticular formation arises from primary afferent fibers. Immunoreactivity to CGRP after rhizotomy however was greatly diminished in the trigeminal sensory complex, confirming the observations of others. Moreover, CGRP immunoreactivity was nearly eliminated in fibers in the lateral parabrachial area, the caudal ventrolateral medulla, both the peri-ambiguus and ventral parts of the rostral ventrolateral medulla, in the external formation of the nucleus ambiguus, and diminished in the caudal pressor area. The nearly complete elimination of CGRP in the lateral reticular formation after rhizotomy suggests this peptide is carried in primary afferent fibers. Moreover, the arborization of CGRP immunoreactive fibers in these areas mimics that of direct projections from the AEN. Since electrical stimulation of the AEN induces cardiorespiratory adjustments including an apnea, peripheral vasoconstriction, and bradycardia similar to those seen in the mammalian diving response, we suggest these perturbations of autonomic behavior are enhanced by direct somatic primary afferent projections to these reticular neurons. We believe this to be first description of potential direct somatoautonomic projections to brainstem neurons regulating autonomic activity.